2018
DOI: 10.1159/000487326
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Assessment of the Role of miRNAs as Biomarkers in Gastroenteropancreatic Neuroendocrine Tumors

Abstract: Background/Aims: A key issue in neuroendocrine neoplasia management is the identification of blood signatures that specifically define the activity of a cancer or local tumor microenvironment. MicroRNAs (miRNAs) may represent such a candidate. To evaluate their clinical utility as biomarkers in gastroenteropancreatic neuroendocrine tumors (GEP-NETs), we assessed their expression in tissue and blood. Methods: A systematic review of PubMed was undertaken to identify studies investigating miRNAs in GEP-NETs and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 101 publications
(153 reference statements)
0
72
0
1
Order By: Relevance
“…miRNA biomarkers [63] either derived from tumour cells or from the local microenvironment have passed the early developmental stages and are now undergoing investigation [90]. Recent longitudinal assessment of miRNA profiling in SBNEN undergoing resection demonstrated an ability to discriminate between SBNEN patients and healthy controls with an area under the curve (AUC) of 0.951, with capabilities in identifying residual and recurrent disease [91].…”
Section: T -Primary Tumourmentioning
confidence: 99%
“…miRNA biomarkers [63] either derived from tumour cells or from the local microenvironment have passed the early developmental stages and are now undergoing investigation [90]. Recent longitudinal assessment of miRNA profiling in SBNEN undergoing resection demonstrated an ability to discriminate between SBNEN patients and healthy controls with an area under the curve (AUC) of 0.951, with capabilities in identifying residual and recurrent disease [91].…”
Section: T -Primary Tumourmentioning
confidence: 99%
“…We are not aware of any studies focused on circulating miRs in EAS or in patients with CD. Nevertheless, circulating miR-182, 196a, 200a, 21-5p, 22-3p, and 7-5p were upregulated and miR-31, 129-5p, 133a, 215, and 150-5p were downregulated in patients with small bowel neuroendocrine tumors (9,(36)(37)(38). Downregulation of miR has been observed in plasma samples of patients with pituitary adenoma compared to samples from healthy subjects (39).…”
Section: Discussionmentioning
confidence: 99%
“…However, the BIPSS procedure is invasive, costly and has certain contraindications and potential complications (7). Bloodcirculating microRNAs (miRs) are current promising biomarkers in cancer diagnosis and monitoring (8,9) as well as in some metabolic diseases (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Altered expression of specific miRNAs has been reported between normal, benign, and malignant tissues of MEN1-associated NETs, including pituitary [ 19 , 20 , 21 ], parathyroid [ 22 , 23 ], and GEP tract [ 24 , 25 ] tumors. Results from a previous study of our Research Group showed that menin is a direct target of miR-24-1, and that this miRNA may contribute to MEN1 parathyroid tumorigenesis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%